2009
DOI: 10.1074/jbc.m109.007104
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Nerve Growth Factor Precursor Is Dependent upon Relative Levels of Its Receptors

Abstract: Nerve growth factor (NGF) is produced as a precursor called pro-nerve growth factor (proNGF), which is secreted by many tissues and is the predominant form of NGF in the central nervous system. In Alzheimer disease brain, cholinergic neurons degenerate and can no longer transport NGF as efficiently, leading to an increase in untransported NGF in the target tissue. The protein that accumulates in the target tissue is proNGF, not the mature form. The role of this precursor is controversial, and both neurotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 52 publications
9
114
0
Order By: Relevance
“…In melanoma cells, it has previously been shown that the addition of proNGF can lead to a stimulation of cell invasion through activation of p75 NTR and sortilin (28); in this model, TrkA was not found to be necessary. However, the activation of TrkA by proNGF has also been reported in other models (8), with the biological activity of proNGF dependent upon relative levels of TrkA versus p75 NTR (29). Therefore, although p75 NTR appears to be mediating proNGF invasive effects in melanoma, in breast cancer, the present study indicates that TrkA is involved without the participation of p75 NTR .…”
Section: Discussionmentioning
confidence: 42%
“…In melanoma cells, it has previously been shown that the addition of proNGF can lead to a stimulation of cell invasion through activation of p75 NTR and sortilin (28); in this model, TrkA was not found to be necessary. However, the activation of TrkA by proNGF has also been reported in other models (8), with the biological activity of proNGF dependent upon relative levels of TrkA versus p75 NTR (29). Therefore, although p75 NTR appears to be mediating proNGF invasive effects in melanoma, in breast cancer, the present study indicates that TrkA is involved without the participation of p75 NTR .…”
Section: Discussionmentioning
confidence: 42%
“…High proNGF concentrations can stimulate PC12 cell survival when the p75NTR/TrkA ratio is low (Fahnestock et al 2004). It was established that the receptors balance, i.e., the relative level of Trk and p75NTR, is a crucial determinant of cell fate during development and that it is required for further modulation of neurite outgrowth/synaptic plasticity in the adult brain (Masoudi et al 2009). ProNGF has indeed been demonstrated to induce neuronal apoptosis in vivo after injury or seizures when p75NTR expression is induced, shifting the balance of signaling towards apoptosis (Volosin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the two receptor types can elicit opposing effects -survival and differentiation via Trks, or apoptosis via p75NTR 9,10 . Adding to the complexity, TrkA and TrkC can act as dependence receptors that elicit apoptosis when unstimulated 11 , and the biological effect of secreted proneurotrophins might depend on the expression ratio of Trk receptors and p75NTR 12,13 and on expression of p75NTR co-receptors 14,15 .…”
Section: Schwann Cells and Their Interactionsmentioning
confidence: 99%